2017
DOI: 10.1039/c7ce01128h
|View full text |Cite
|
Sign up to set email alerts
|

Compositional effect of complex biorelevant media on the crystallization kinetics of an active pharmaceutical ingredient

Abstract: Bile salts are endogenous surfactants present in the human gastrointestinal tract in the form of mixed micelles that also contain phospholipids. Due to the inevitable encounter of oral drug formulations with bile salts, it is important to understand the impact of bile salts on the crystallization tendency of poorly soluble compounds that form supersaturated solutions in vivo in order to maximize oral drug absorption. Although there has been an increasing number of studies focusing on the role of individual bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…The observation that NaTc and porcine bile extract (a mixture of bile salts) can prolong the supersaturation of CFZH + , also correlates well with previous studies conducted by Chen et al,Li et al and Lu et al [3], [18]- [21], which showed how the crystallization of hydrophobic drugs can be slowed and in some cases prevented by the presence of NaTc and other bile acids [3], [18]- Highlighted by a red border in Figure 5 is a region of the CFZB crystal, where circular arrangements of CFZ hydrochloride crystals have nucleated onto the surface of the free base. As CFZB dissolved in 25 mM HCl, the surface of the dissolving crystals appears to provide a template onto which the HCl salt can nucleate and grow.…”
Section: Screening the Impact Of Polymers Bile Salts And Pepsin On Tsupporting
confidence: 89%
See 2 more Smart Citations
“…The observation that NaTc and porcine bile extract (a mixture of bile salts) can prolong the supersaturation of CFZH + , also correlates well with previous studies conducted by Chen et al,Li et al and Lu et al [3], [18]- [21], which showed how the crystallization of hydrophobic drugs can be slowed and in some cases prevented by the presence of NaTc and other bile acids [3], [18]- Highlighted by a red border in Figure 5 is a region of the CFZB crystal, where circular arrangements of CFZ hydrochloride crystals have nucleated onto the surface of the free base. As CFZB dissolved in 25 mM HCl, the surface of the dissolving crystals appears to provide a template onto which the HCl salt can nucleate and grow.…”
Section: Screening the Impact Of Polymers Bile Salts And Pepsin On Tsupporting
confidence: 89%
“…The driving force for the common ion effect for weakly basic ionisable APIs is an increase in counterion concentration, which shifts the solubility equilibrium of the dissociated reaction to favour crystallization of the solid salt form of the API. The use of synthetic polymers, and recently of bile salts, to inhibit the crystallization of hydrophobic APIs is well described in the literature [3], [14]- [17], [21], [37], [38] This complements our previous study which shows how solution concentration and stability of CFZH + at pH 1.6 (in 25 mM HCl) depends on the presence and concentration of NaTc, lecithin, and pepsin in the system [22]. These results explain that the underlying mechanism for this manipulation of solution behaviour was through interference with the crystallization kinetics of CFZ hydrochloride from these solutions, with the exception of pepsin.…”
Section: Screening the Impact Of Polymers Bile Salts And Pepsin On Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed micelles obtained from a mixture of several bile salts and lecithin were shown to inhibit the precipitation of supersaturated telaprevir solutions. 23 By contrast, no effect was observed for sodium taurocholate and lecithin (FaSSIF) compared to buffer. 23 With respect to the solubilizing capacity, the chain length and saturation number of phospholipids were found to be related to their drug solubilizing capacity.…”
Section: Discussionmentioning
confidence: 98%
“…23 By contrast, no effect was observed for sodium taurocholate and lecithin (FaSSIF) compared to buffer. 23 With respect to the solubilizing capacity, the chain length and saturation number of phospholipids were found to be related to their drug solubilizing capacity. 24 In the current study, the thermodynamic solubility of ketoconazole was not affected by aged FaSSIF, which is in line with the thermodynamic equilibrium after the transfer experiments.…”
Section: Discussionmentioning
confidence: 98%